A Systematic Review about Cervical Pregnancy and our Experience - Nikolettos, Konstantinos; Oikonomou, Efthymios; Kotanidou, Sonia; Kritsotaki, Nektaria; Kyriakou, Dimitrios; Tsikouras, Panagiotis; Kontomanolis, Emmanouil; Gerede, Angeliki; Nikolettos, Nikos (Acta medica Lituanica, 2024)
Background: Cervical ectopic pregnancy is a relatively rare type of ectopic pregnancy and has no standardized guidelines for management.Methods: This systematic review is based on the collection of case reports, published in PubMed/MEDLINE about the resolution of ectopic cervical pregnancies over the last decade and the presentation of a case managed in our healthcare unit. Studies involving cervical pregnancy in the first trimester with the presence of a viable embryo and β-hCG in the serum below 100.000 mIU/mL were included, while heterotopic pregnancies were excluded.Results: Nineteen articles reporting twenty-three case reports are demonstrated explicitly emphasizing on the management techniques. There is no established approach for the management of this type of ectopic pregnancy.Conclusion: It is important to consider the conservative approaches as first-line treatment in all cases of cervical pregnancy preserving fertility. Minimally invasive methods are also described and preferred as second-line treatment, as reported in our literature review.